SISTEM PELAYANAN ONLINE PADA SD NEGERI 62 KOTA BENGKULUMENGGUNAKAN ADOBE DREAMWEAVER CS4 - yono, Hari Aspri; Jauhari, Jauhari (UNIVED Press, 2012)
This study aimstohelpprovidea web-based informationvia theinternetatBengkulupeoplewhoneed informationElementary School62Bengkulu cityandcan be accessedanywhereandanytimeby enteringthe website address, study aims to determineandadd insight andexperiencein makingthe programwebsiteandalsoforother types of programs. With the websiteatElementary School62Bengkulu city, then theprocess ofgivinginformationabout theprofileandotherinformationto visitorstohelpthemget the information theyneed.Becausein this websitewilldisplaya varietyof informationthat is needed byvisitors.